On education - Russell, Bertrand (Routledge classics, 2010)
Bertrand Russell is considered to be one of the most significant educational innovators of his time. In this influential and controversial work, Russell calls for an education that would liberate the child from unthinking obedience to parental and religious authority. He argues that if the basis of all education is knowledge wielded by love then society can be transformed. One of Bertrand Russell's most definitive works, the remarkable ideas and arguments in On Education are just as insightful and applicable today as they were on first publication in 1926.